A simulation of outrigger canoe paddling performance - Caplan, N. (The Engineering of sport 7, Volume 1, 2008)
The main performance variable in outrigger canoeing is boat velocity. The aims of this study were to derive a model of the mechanics of the outrigger canoeing (O1) stroke and to perform a sensitivity analysis to determine the key variables for increasing boat velocity. The model considered the fluid dynamic interaction between the paddle and water, the oscillatory motions of the paddler's upper body relative to the boat, the mass of the paddler and boat, and stroke rate. Due to the identical hulls between the O1 and K1 boats, measured hydrodynamic drag relationships for a K1 kayak were used. The aerodynamic drag acting on the paddler was assumed to be similar to that of a seated man. The model was solved using a fourth order Runge-Kutta solver with a fixed time Step of 0.001s. The model was validated against the mean boat velocity for an elite female paddler over a 500m race distance. The paddler was filmed in order to determine the linear and angular trajectories of the paddle and the paddler's centre of mass through the stroke. A sensitivity analysis was then performed by increasing/decreasing each input variable by 1%, A difference of less than 3% was observed between modelled and measured mean boat velocity showing the model to be valid. The sensitivity analysis showed that the key variable influencing boat velocity was horizontal paddle velocity relative to the boat. The degree to which this variable can be increased is influenced by the strength of the paddler. The next most sensitive variables were the paddle's size and maximum drag coefficient. The magnitude of maximum drag coefficient is a function of the paddle design. Future research should now focus on determining the underlying mechanisms contributing to the increases in boat velocity elicited by changes to these key variables.